M*A*S*H. Season two [videorecording (DVD)] - Gelbart, Larry; Metcalfe, Burt; Alda, Alan, 1936-; Rogers, Wayne, 1933-2015; Stevenson, McLean; Swit, Loretta; Linville, Larry, 1939-2000; Burghoff, Gary; Hooker, Richard (Twentieth Century Fox Home Entertainment, 2008)
Explores the day-to-day lives of the people who live and work at the Mobile Army Surgical Hospital (MASH) stationed three miles from the front during the Korean War.